The effects of DDX4-deletion on PC3 tumour formation, growth and transcriptome - Louramo, Elina (My University, 2024)
Cancer-germline (CG) antigen-genes are a set of genes normally expressed in germ cells, trophoblasts and a few somatic tissues but also aberrantly expressed in a wide range of human malignancies. Cancer cells share multiple functional characteristics with germ cells, such as hyperproliferation and extensive migration, and it has long been proposed that cancer cells harness their reservoir of normally silent germline genes to adapt and face challenges in their new environment. Germ cells are characterized by germline specific ribonucleoprotein granules, also known as germ granules. The germ granules appear in the cytoplasm of germ cells during haploid differentiation and serve as an important platform for coordinating different RNA-regulatory pathways. Interestingly, components of the germ granules are also cancer-germline antigens, suggesting a role in cancer formation and progression. One of the main germ granule components, DEAD-box helicase 4 (DDX4), appears in the cytoplasm of several human cancers. This thesis aims to elucidate the effects of DDX4 deletion on tumor transcriptome and xenograft tumor formation in immunodeficient mice. Our data revealed that DDX4-deletion does in fact hinder tumor formation, growth, progression and likely metastasis in xenograft tumor models. In addition, DDX4-deletion has major effects on tumor transcriptome. Therefore, research on DDX4 and its role in cancer could provide valuable information regarding its utility as a marker for certain cancers or even as a therapeutic target. In addition, the results stress the need to validate RNA-sequencing results.
Keywords: cancer germline antigen gene, DDX4, germ granule